2018
DOI: 10.20903/csnmbs.masa.2018.39.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Prospects of Square-Wave Voltammetry

Abstract: This review concerns recent methodological advances of square-wave voltammetry as one of the most sophisticatedmembers of the pulse voltammetric techniques. Besides addressing recent theoretical works and representatives ofadvanced analytical studies, an emphasis is given to a few novel methodological concepts such as kinetic analysis atconstant scan rate, cyclic square-wave voltammetry, multisampling square-wave voltammetry, and electrochemical faradaicspectroscopy. For the purpose of improving analytical per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…As shown the above figure, two completely resolved peaks are observed at activated glassy carbon electrode and the E p of uric acid was observed at positive potential ( ̴ 25 mV) with activated glassy carbon electrode also the potential peak to separation of the two analytes were 90 mV. The well-defined peak of paracetamol was obtained at activated glassy carbon electrode with good peak separation from Uric acid [12,28,35]. Generally, the above voltammogram was observed that Uric acid affect peak current for paracetamol compared with paracetamol without Uric acid under the potential range used (i.e decrease the peak current and causes to the broadness of the peak of paracetamol), but do not affect the peak potential of paracetamol.…”
Section: Interference Study On the Behaviour Of Paracetamolmentioning
confidence: 75%
“…As shown the above figure, two completely resolved peaks are observed at activated glassy carbon electrode and the E p of uric acid was observed at positive potential ( ̴ 25 mV) with activated glassy carbon electrode also the potential peak to separation of the two analytes were 90 mV. The well-defined peak of paracetamol was obtained at activated glassy carbon electrode with good peak separation from Uric acid [12,28,35]. Generally, the above voltammogram was observed that Uric acid affect peak current for paracetamol compared with paracetamol without Uric acid under the potential range used (i.e decrease the peak current and causes to the broadness of the peak of paracetamol), but do not affect the peak potential of paracetamol.…”
Section: Interference Study On the Behaviour Of Paracetamolmentioning
confidence: 75%
“…The benefits of voltammetric techniques reside in their marvelous sensitivity, quick analysis, concurrent detection of different analytes, generation of different potential waveforms, small current measurements and determination of kinetic parameters. Voltammetric biosensing methods can be based on polarographic, stripping voltammetric, linear scan or sweep voltammetric, differential pulse voltammetric (DPV), normal pulse voltammetric (NPV) or CV measurements [255][256][257][258][259].…”
Section: Voltammetric Gqd-sensorsmentioning
confidence: 99%
“…The SWV excitation response constitutes a defined symmetry like a 'staircase pattern' (Figure 15B). SWV is a widely used method, because its advantages lie in providing excellent sensitivity and increased signal/noise ratio [258,259]. Moreover, the typical SWV peak right from the electrode functionalization to the target detection is displayed in Figure 15C.…”
Section: Voltammetric Gqd-sensorsmentioning
confidence: 99%
“…Voltammetric sensing techniques include cyclic voltammetry, linear sweep/scan voltammetry, differential pulse voltammetry, square wave voltammetry, polarography, and stripping voltammetry. A two-or three-electrode electrochemical sensor containing a potentiostat can be employed to measure the current [95][96][97][98][99].…”
Section: Voltammetric Sensorsmentioning
confidence: 99%
“…The peak height is directly proportional to the concentration of the electroactive species. SWV exhibits excellent sensitivity, ignores background currents, and enhances the signal to noise ratio [98,99]. Figure 5E depicts the SWV response with respect to the different steps tangled from the electrode modification to the analyte determination.…”
Section: Voltammetric Sensorsmentioning
confidence: 99%